Identity (Manajemen Konflik) - Dewi Nursidah; Annisa Tri Azzahra; Ariel Achmad; Sintia Sintia; Siradjuddin Siradjuddin (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the role of identity in organizational dynamics and its relationship with internal conflict. A literature review method was employed, examining various theories regarding social identity and conflict management. The findings indicate that identity is an individual's self-perception formed through group membership (ingroup) and comparisons with other groups (outgroup). Identity plays a dual role: acting as a conflict trigger through in-group favoritism and discrimination, yet also serving as a means of integration through the formation of a superordinate identity. Sharp identity-based differences can spark destructive conflict, whereas inclusive identity management can foster synergy and innovation. Understanding identity dynamics is crucial for managers seeking to create a harmonious work environment and enhance organizational performance.